2019
DOI: 10.3390/molecules24071326
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Frequencies of Chlorophyll f and Chlorophyll a and Evaluation of Displacement through Franck-Condon Progression Calculations

Abstract: We present ground and excited state frequency calculations of the recently discovered extremely red-shifted chlorophyll f. We discuss the experimentally available vibrational mode assignments of chlorophyll f and chlorophyll a which are characterised by particularly large downshifts of 131-keto mode in the excited state. The accuracy of excited state frequencies and their displacements are evaluated by the construction of Franck–Condon (FC) and Herzberg–Teller (HT) progressions at the CAM-B3LYP/6-31G(d) level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Final gas-phase geometry optimizations were performed using CAM-B3LYP along with def2-TZVP basis sets, with the inclusion of dispersion corrections via the D3­(BJ) scheme. , The choice of the functional was motivated by the observation that it provides better balance in the description of low- and high-energy states compared to other functionals, as well as in order to ensure the consistency of methods between geometry optimization and calculation of ground- and excited-state frequencies. In addition, a recent study demonstrated an improved performance of CAM-B3LYP over B3LYP for the prediction of the vibronic spectrum for both Chl a and Chl f . The RIJCOSX approximation , was used to speed up the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Final gas-phase geometry optimizations were performed using CAM-B3LYP along with def2-TZVP basis sets, with the inclusion of dispersion corrections via the D3­(BJ) scheme. , The choice of the functional was motivated by the observation that it provides better balance in the description of low- and high-energy states compared to other functionals, as well as in order to ensure the consistency of methods between geometry optimization and calculation of ground- and excited-state frequencies. In addition, a recent study demonstrated an improved performance of CAM-B3LYP over B3LYP for the prediction of the vibronic spectrum for both Chl a and Chl f . The RIJCOSX approximation , was used to speed up the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…However, CAM-B3LYP has been shown to describe the structural features of chlorophyll monomers very well. 47 , 172 For the B3LYP optimized structure, we can compare our herein calculated VEEs to the ones from Hashemi and Leppert calculated on the same level of theory. Except for the Q x excitation energies, which are slightly different (40 meV), we find a perfect agreement between both implementations.…”
Section: Resultsmentioning
confidence: 99%
“…We carried out an ab initio study on the physical properties of 2D-HOIPS, focusing on (RNH 3 ) 2 (MA) n−1 B n X 3n+1 (R: long-chain alkyl or aromatic group; n : the number of metal-halide sheets), and the effects of phase, thickness and surface molecule based on density-functional theory (DFT) [43,44,45,46] and Perdew-Burke-Eznerhof generalized gradient approximation (PBE-GGA) [47,48] to accurately calculate the total energy. The Vienna ab initio simulation package (VASP) with the projector augmented wave (PAW) scheme was used [46,49,50].…”
Section: Computational Detailmentioning
confidence: 99%